A Call for the World Health Organization to Create International Classification of Disease Diagnostic Codes for Post‐Intensive Care Syndrome in the Age of COVID‐19. Issue 2 (22nd February 2021) - Peach, Brian C.; Valenti, Michael; Sole, Mary Lou
Abstract : Post‐intensive care syndrome (PICS), a condition found in survivors of critical illness, is characterized by persistent physical, cognitive, and psychological sequelae that impact the quality of life after discharge from an intensive care unit (ICU). At present, there are no International Classification of Disease (ICD) billing codes for this condition. Without financial alignment, clinicians cannot diagnose PICS, hindering tracking of its prevalence and impeding policy development for this condition. Clinicians should be screening for PICS in all survivors of critical illness, particularly those with acute respiratory distress syndrome (ARDS). Results from single‐center studies suggest over 75 percent of ARDS survivors develop PICS. With nearly 5 percent of patients with COVID‐19 requiring ICU admission for ARDS, it is important for clinicians to be able to diagnose PICS in survivors, and researchers to be able to track it. Member states should impress upon the World Health Organization to create ICD‐10 codes for PICS.